Dissolution of Copper from Smelting Slag by Leaching in Chloride Media - Dimitrijevic, Mile D; Urošević, Daniela M; Milić, Snežana M; Sokić, Miroslav D; Marković, Radmila T (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
Leaching of copper smelting slag in chloride media was studied. The lixiviants used were aqueous solutions of hydrochloric acid (0.5-2.0 M HCl) as well as hydrogen peroxide and hydrochloric acid (0.5-3.0 M H2O2, 1.0 M HCl). The maximum final copper extraction from the slag of 73% was attained with 3 M H2O2, at room temperature after 120 minutes of reaction. At the same time, 55% of the iron from the slag was also dissolved. The copper extraction increased during the first 60 minutes of reaction and essentially ceased thereafter. Because of a rapid catalytic decomposition of hydrogen peroxide, it should be added contiuously to the leach suspension rather than at once at the begining of the experiment. In fact, it appears that almost complete dissolution of copper from the slag is achievable after about 4 hours of leaching by implementing the method of continuous lixiviant addition. Also, it seems that the final iron extraction could be limitied to as low as 20% by using this method.